2006
DOI: 10.3201/eid1209.060200
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Outbreak, India, 2005

Abstract: An outbreak of viral encephalitis occurred in Gorakhpur, India, from July through November 2005. The etiologic agent was confirmed to be Japanese encephalitis virus by analyzing 326 acute-phase clinical specimens for virus-specific antibodies and viral RNA and by virus isolation. Phylogenetic analysis showed that these isolates belonged to genogroup 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 10 publications
4
88
0
Order By: Relevance
“…JEV, the most common causative agent of AES detected in this study, has also been reported as the chief cause of encephalitis in tropical countries, which occurs both sporadically and in outbreaks and has mortality rates ranging from 20z to 40z (9)(10)(11). A large proportion of AES patients were found to be positive for DV.…”
Section: Discussionmentioning
confidence: 78%
“…JEV, the most common causative agent of AES detected in this study, has also been reported as the chief cause of encephalitis in tropical countries, which occurs both sporadically and in outbreaks and has mortality rates ranging from 20z to 40z (9)(10)(11). A large proportion of AES patients were found to be positive for DV.…”
Section: Discussionmentioning
confidence: 78%
“…22 This difference in etiological findings of suspected AES cases is due to the geographic features of this region which favour in spread of JEV-an abundance of rice fields and high temperature and relative humidity, provides a suitable environment for JEV transmission. 23 UP alone contributes to 70-75% of total disease burden in India. 7 However, Bhatt GC et al conducted a cross-sectional study on clinic-laboratory profile of acute encephalitis syndrome on 100 patients in the eastern Uttar Pradesh region of India.…”
Section: Diagnosismentioning
confidence: 99%
“…[1][2][3] Over the past three decades, the incidence of Japanese encephalitis (JE) has increased in parts of India, Nepal, and southeast Asia, with outbreaks of JE occurring in several areas that were previously not endemic for this disease. 2,[4][5][6][7][8][9] The reasons for this increased geographic distribution are uncertain, but may include population shifts, and changes in agricultural practices, animal husbandry, migratory bird patterns, and movement of vector mosquitoes to wider areas. 1 It is estimated that JEV causes at least 50,000 cases of encephalitis each year in Asia, resulting in approximately 10,000 deaths with 15,000 survivors developing neurological and psychiatric sequelae.…”
Section: Introductionmentioning
confidence: 99%